Sprache und Vertrauen: Facetten der linguistischen und interdisziplinären Vertrauensforschung - Schäfer, Pavla; Belošević, Milena (Sprache und Wissen, 2024)
Trust depends on communication in all life domains – whether in private life, institutions, medicine, education, or other areas. The mechanisms of trust vary, reflecting their diversity. What is the relationship between trust and language? This question requires a nuanced response. This edited volume focused on the linguistic perspective, combining it with facets from neighboring disciplines
Literaturangaben
Keywords: Konferenzschrift -- 2021 -- Online; Psycholinguistik; Vertrauen; Kommunikation; Sprache; Deutsch